Angioedema: Clinical and etiological aspects - Kanokvalai Kulthanan (2018)
Angioedema is an abrupt swelling of the skin, mucous membrane, or both including respiratory and gastrointestinal tracts. This study aimed to report an experience of angioedema in a university hospital with respect to etiologies, clinical features, treatment, and outcome. One hundred and five patients were enrolled. About half had angioedema without urticaria. The common sites of involvement were periorbital area and lips. Forty five patients (49%) had systemic symptoms. The most common cause of angioedema was allergic angioedema. Nonsteroidal anti-inflammatory drug-induced angioedema and idiopathic angioedema were detected in 20% and 18%, respectively. Among patients with allergic angioedema, 41.7% were caused by food, 39.6% by drugs. Thirty seven patients (39%) had recurrent attacks of angioedema. Mean standard deviation (SD) number of attacks in patients with recurrent angioedema was 3.9 (2.7) (ranging from 2 to 10 times). Patients who had older age and multiple sites of skin involvement had tendency to have systemic symptoms. Copyright © 2007 Kanokvalai Kulthanan et al.